Aβ‐reactive T cell polyfunctionality response as a new biomarker for mild cognitive impairment - Yen‐Ling Chiu; Sui‐Hing Yan; Yang‐Teng Fan; Chiung‐Fang Chang; Ruo‐Wei Hung; Yi‐Chien Liu; TienYu Owen Yang; Yi‐Fang Chuang (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring)
Abstract Introduction Alzheimer's disease (AD) involves neuroinflammation and amyloid plaque deposition, yet the role of amyloid‐reactive immune response in neurodegeneration remains unclear. We investigate amyloid‐reactive T cell levels in the Epidemiology of Mild Cognitive Impairment Study in Taiwan (EMCIT) and Taiwan Precision Medicine Initiative of Cognitive Impairment and Dementia (TPMIC) cohorts. Method Using diverse amyloid peptide formulations, we established a polyfunctionality assay for five T cell functions and compared mild cognitive impairment (MCI) patients to control subjects in both cohorts. Results In both cohorts, MCI individuals exhibit higher amyloid‐reactive T cell responses than controls. In the TPMIC cohort, CD4+ and CD8+ total response frequencies are notably elevated in MCI (CD4: 1.3%, CD8: 1.91%) versus controls (CD4: 0.15%, CD8: 0.28%; both p < 0.001). Amyloid‐reactive T cell response outperforms plasma phosphorylated tau 181 (p‐tau181) in discriminating MCI (area under the receiver operating characteristic curve CD4+: 0.97; CD8+: 0.96; p‐tau181: 0.72; both p < 0.001). Discussion Amyloid‐reactive T cell polyfunctional response distinguishes MCI from normal aging and could serve as a novel MCI biomarker. Highlights Amyloid‐reactive polyfunctional T cell responses can be detected in the peripheral circulation. Amyloid‐reactive T cell response is significantly enhanced in individuals with mild cognitive impairment compared to age‐matched, cognitively unimpaired individuals. The unique discriminative accuracy of amyloid‐reactive T cell response is significantly higher than phosphorylated tau181 and is not a result of overall T cell hyperreactivity. Future studies are needed to determine the predictive role of amyloid‐reactive T cell responses in disease progression and if the amyloid‐reactive immune response could be a therapeutic target for the treatment of neurodegeneration.